Economic Analysis of Mandarin (Citrus reticulata) Production in Salyan District of Nepal - Dahal, Shishir; Dangi, Bijaya; Dangi, Raman Kumar; Bista, Prakash; Upadhyaya, Ashmita Sharma; Bharati, Sunita; Dulal, Sunil (International Journal of Applied Sciences and Biotechnology, 2023)
Mandarin (Citrus reticulata) is the major sub-tropical fruit popularly grown in slopy terraces of mid-hills which has high domestic and foreign market potentialities. Scientific studies are hardly carried out to assess the socio-economic aspects of mandarin production in this area. So, this research was aimed to assess the production and profitability of mandarin production in Salyan district. For this, 61 respondents of Baghchaur municipality and 59 of Chhatreshwari rural municipality were selected using random sampling procedure which makes altogether 120 respondents in the study area. Pretested semi structured questionnaire were asked with farm decision makers for primary data collection. Collected data were encoded in MS excel version 2021, and required inferences on socio-economic and demographic characteristics, BC ratio, cobb-douglas production function and problem ranking were made by using SPSS version 26. Independent t test was used to compare the means between two municipalities. The results revealed that the annual mandarin production was 3560.58 Kgs per household with productivity of 14.60 tons per hectare. Average annual variable cost of production and revenue were NRs 227309.41 and NRs 988963.52 per hectare respectively. BC ratio was 5.07 indicating it as profitable business with the benefit of NRs 4.07 per rupee invested. Among the various determinants, cost of organic manure, human labor and plant protection materials had significantly increased while cost of irrigation had decreased the returns from the enterprise at different significance levels. The return of scale was 0.936 indicating decreasing rate of return of mandarin production. Int. J. Appl. Sci. Biotechnol. Vol 11(2): 106-115.